[LB.01.33] DRUG ADHERENCE AND CLINICAL OUTCOME IN RESPONSE TO PERINDOPRIL/AMLODIPINE FIXED DOSE COMBINATION IN AN ITALIAN CLINICAL PRACTICE SETTING. THE AMLODIPINE-PERINDOPRIL IN REAL SETTINGS (AMPERES) STUDY. (September 2017) - Borghi, C.; Esposti, L. Degli; Perrone, V.; Buda, S.
Abstract : Objective: The purpose of this study was to assess in real practice the effect on adherence of a switch from a single- or two-pills therapy (SPT/FC) of perindopril and/or amlodipine to fixed-dose combination (FDC) of the same drugs. Methods: This was a retrospective cohort study, performed in 3 Italian Local Health Units. We selected all subjects ? 18 years, who received at least one prescription of antihypertensive drugs between 01/01/2010 and 31/12/2014. For each patient we evaluated the adherence to different schedule of perindopril/amlodipine administration schedule during the two 12-month periods preceding and following the index date. We also evaluated the rate of major CV events, the changes in concomitant treatment and the economic implications of drugs switch. Changes in adherence level had been compared in subjects who shifted to the FDC of perindopril/amlodipine after the ID as well as in patients who did not. Design and method: A total of 24, 020 subjects were analyzed. Subjects treated with the free dose combination switched more frequently to FDC of to perindopril/amlodipine than subjects treated with SPT (p < 0.001). Adherence to treatment was higher in the 3, 597 subjects who switched to the perindopril/amlodipine FDC therapy, than in the 20, 423 subjects who did not. The rate of major CV events was lower in patients with adherence > 80% who also showed a higher rate of concomitant treatment reduction (36.5% vs. 21.3%; p = 0.005). No differences have been observed in the drug costs after switch. Results: Our results show that, the real-world use of perindopril/amlodipine as FDC increases the rate of stay-on-therapy, improves the antihypertensive drug schedule and reduces the rate of major CV events in subjects previously treated with the same drugs as a two pills combination or as SPT.